The Influence Of Insurance Service Reputation, Customer Relationship Management, And Price Attractiveness On Insurance Service Customer Customer Experience: A Literature Review - Rio Sukmawan; Zulganef Zulganef (Research Collaboration Community (RCC), 2023)
In the service industry, a positive company reputation will influence customers' decisions to choose that business for their insurance needs. This reputation is systematically built by upholding the importance of responsibility and engaging in open dialogue with clients to foster a sense of client loyalty to insurance services. Customer loyalty is significantly influenced by customer relationship management. The most crucial thing for management to do is to uphold trust and service standards so that clients are satisfied with the products and services the business offers. Price is not only significant to customer service but also a key indicator of service quality. Client experience can influence a customer's trust in a company. The purpose of this literature review is to provide an overview of previous research on the impact of insurance service reputation, customer relationship management, and price attractiveness on insurance service customers' experiences. The method used is a literature review, which is a study that collects, comprehends, analyzes, and then concludes national and international journals. The findings of this literature review show that there is a relationship between customer loyalty and customer experience and the reputation of insurance services. Additionally, there is a relationship between customer relationship management and price attractiveness on customer loyalty and customer experience.